Parents and their Needs for Information and Communication with School - Gera, Rina; Hoti, Irida (Mediterranean Journal of Social Sciences, 2012)
The communication teachers –parents is going to be even more essential for the progress of the child. So it tends to be directand all inclusive with the aim of evidencing the progress of the success of the child. The information, is very important in transmitting thechanges and the new ideas in the educational process, as a primary form of communication .This study tends to analyze some problemsfaced in information and as a result in communication parents - teachers. To highlight these problems we have done a questionnaire withapproximately 100 parents of primary and secondary school children, from which we tend to present that the information in our schools isnot in the required expectations, especially in public schools. In non-public schools, in which the information is more formal andinstitutional toward every parent are also evaluated some details and elements as: parents meeting, school activities, tests etc.,consequently the communication is more different in the simplicity, objectivity in evaluation and judgment. On the other hand this studytends to bring different forms of communication, which are applicable nowadays in Shkodra city schools. Also what they suggest to do intheir point of view, what they want from the school, how they want to collaborate with teachers and other staff to be more fruitful andsuccessful for their children.